ERSEPSI PENGGUNA INTERNET DI INDONESIA DALAM KAITAN DENGAN HAK ASASI MANUSIA - Subekti, Slamet (Faculty of Humanities, Diponegoro University, 2013)
ABSTRACT This paper discusses the perception of the Internet user in Indonesia in relation to human rights. The data compiled from the result of Global Internet User Survey (GIUS) 2012. Based on their survey it can be concluded that the Internet user in Indonesia has a positive attitude, they considered that it is an essential vehicle for promoting the human rights. In turn, the necessary awareness among the Internet user in Indonesia to obey the Cyber Ethics in order to support the dialogue between local wisdom and global culture. Keywords: Internet user in Indonesia, human rights, GIUS 2012.